Análise da alocação de recursos por proprietários e parceiros em áreas de agricultura de subsistência - Garcia , João Carlos; Barbosa , Túlio; Teixeira Filho, Antônio Raphael; Batista de Oliveira , Evonir (Revista Ceres, 2025)
The objective of this study was to analyze the economic efficiency of resource allocation by owners and sharecroppers in a region of subsistence agriculture.